THE USE OF BLENDED LEARNING TO IMPROVE STUDENTS’ SELF DIRECTED LEARNING IN ACCOUNTING CLASS AT SMK N 7 YOGYAKARTA ACADEMIC YEAR OF 2014/2015 - Yolandaru Septiana; Annisa Ratna Sari (Universitas Negeri Yogyakarta, 2015)
Based on the pre-research questionnaire in accounting introduction class at SMK N 7 Yogyakarta, 64,68% students have self management, 75,00% students have desire for learning and 71,00% students have characteristics of self control. This shows the self directed learning is low. Thus, the type of this research aimed to improve students’ Self Directed Learning of Class X AK 1 SMK N 7 Yogyakarta Academic Year of 2014/2015. The research is done in two cycles uses one kinds of data collection techniques is questionnaire. The data collected was analyzed by qualitative analysis using three steps, data reduction, data presentation and conclusion formulation. The analysis is completed with descriptive quantitative analysis to calculate the score of Self Directed Learning. Based on the research result, the implementation of Blended Learning is able to improve students’ Self Directed Learning of the class X AK 1 SMK N 7 Yogyakarta academic year of 2014/2015. It is proven by the improvements of X AK 1’s average score of Self Directed Learning from 73,66% on the first cycle and reaches to 79,60% on the implementation of the second cycle. This improvement shows that using Blended Learning is able to improve students’ Self Directed Learning of class X AK 1 SMK N 7 Yogyakarta. Keywords: Blended Learning, Self Directed Learning, Accounting Class